2020
DOI: 10.1093/g3journal/jkaa038
|View full text |Cite
|
Sign up to set email alerts
|

Chasing breeding footprints through structural variations inCucumis meloand wild relatives

Abstract: Cucumis melo (melon or muskmelon) is an important crop in the family of the Cucurbitaceae. Melon is cross pollinated and domesticated at several locations throughout the breeding history, resulting in highly diverse genetic structure in the germplasm. Yet, the relations among the groups and cultivars are still incomplete. We shed light on the melonbreeding history, analyzing structural variations ranging from 50 bp up to 100 kb, identified from whole genome sequences of 100 selected melon accessions and wild r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…The substantial intra-chromosomal rearrangements spanning nearly half of chromosome 6 that differ between our parents also appears in the recently published de-novo assemblies of “Payzawat” and ‘Harukei-3′ genomes [ 51 , 52 ]. Previous SVs reported in melon, mainly attributed to transposable elements and some to meiotic crossovers [ 32 , 33 , 49 , 50 ], but these studies were focused on events of relatively small DNA fragments (<0.5 Mb). Examples for large-scale rearrangements have been reported in barley, including two frequent large inversions (>5 Mb) found in elite barley lines that are attributed to mutation breeding and the expansion of geographical range [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The substantial intra-chromosomal rearrangements spanning nearly half of chromosome 6 that differ between our parents also appears in the recently published de-novo assemblies of “Payzawat” and ‘Harukei-3′ genomes [ 51 , 52 ]. Previous SVs reported in melon, mainly attributed to transposable elements and some to meiotic crossovers [ 32 , 33 , 49 , 50 ], but these studies were focused on events of relatively small DNA fragments (<0.5 Mb). Examples for large-scale rearrangements have been reported in barley, including two frequent large inversions (>5 Mb) found in elite barley lines that are attributed to mutation breeding and the expansion of geographical range [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Out of the 1412 genes missing from either “Tam Dew” or “Dulce”, none were found within a QTL interval. Nonetheless, recent publications report on PAVs related to melon domestication in a region on chromosome 5 containing resistance genes, such as the protein coding Vat ( Virus aphid transmission ) [ 49 , 50 ]. Though “Tam Dew” and “Dulce” are both elite cultivars ( C. melo ssp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several studies have reported CNV events across various crop species, including rice [ 27 , 36 ], wheat [ 85 ], barley [ 86 ], maize [ 52 , 87 ], soybean [ 46 ], melon [ 88 ] and cannabis [ 89 ]. Most of these studies have linked CNV analysis with agronomic traits.…”
Section: Discussionmentioning
confidence: 99%
“…Domínguez et al ( 2020) found associations of transposon element insertion polymorphisms with major agronomic traits and secondary metabolites in cultivated tomato. Similarly, evidence of the role of retrotransposons on the evolution of the genome and modification of gene expression has also been reported in melon (Demirci et al 2021;Sanseverino et al 2015;Yano et al 2020). Thus, fsqs8.1 is perhaps another case of gene expression changes due to structural variation mediated by transposon activity.…”
Section: Discussionmentioning
confidence: 77%